ANTICIPATION GUIDE TO IMPROVE READING SKILL OF JUNIOR HIGH SCHOOL STUDENTS - Dimas Wahyu Wibowo (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2018)
Reading is important for everybody, because ones can get new knowledge in this globalization era. The students can open up new world with reading and get new point with it. Reading is a basic life skill of students success in school and consequently through life. Without the ability to read effectively, the students can not improve their reading skill. Hence, the aims of the this research were to know whether Anticipation Guide  strategy can improve students reading skill and to describe the class condition when Anticipation Guide strategy was implemented in teaching learning process at the Eight grade of SMP N 4 Sukoharjo in Academic Year 2017/2018. This research was conducted at the Eight grade of SMP N 4 Sukoharjo. The method of the study was classroom action research which was conducted from August to December 2017. The data was collected through test and non-test. In collecting data was used multiple choices in pre test, post test 1, and post test 2. Besides that to collect  non-test was used observation, interview, and documentation. While, to analyze the data was used t-test. The results of the research showed that the implementation of Anticipation Guide   strategy was successful to improve students reading skill. The mean score increased from 50.62 in pre-test became 60.15 in post test 1  until 76.15 in post test 2. T-test was used to compare the significance of teaching reading skill with df = n-1 = 31. In t-table values, significance 5% was 2.040 and significance 1% was 2.744. The result from pre- test and post-test 1 was significance which 2.040 < 3.10 > 2.744. It can be concluded that there was significance difference from pre-test score and post-test 1. Then the result of analysis by using t-test between post-test 1 and post-test 2 was . Then t-test result between post-test 1 and post-test 2 were higher 2.040 < 4.80 > 2.744. A significance improvement between post-test 1 and post-test 2 could be seen clearly from that. In addition, the findings of teaching and learning process showed that there was a change of classroom situation before and after Anticipation Guide was implemented. In addition, the understanding of teaching and learning process show that there is a change of classroom situation after Anticipation Guide strategy is implemented. It can be showed that the students are enjoyable in the learning process when the students active in learning process. Key  words:  Reading  Skill;  Anticipation  Guide  (AG)  strategy;  Classroom  ActionResearch